Management Strategy for The Development of the Creative Economy Through the Design of a Film Curriculum Module for Students in Banyumas Raya Using the Quadruple Helix Model - Oktari, Tepy; Rosyadi, Slamet; Faozanudin, Muslih (Journal Public Policy, 2024)
Film is a subsector of the creative economy experiencing significant growth in Indonesia, with a rate of 10.28%, and is also included in the eight development agendas of the National Long-Term Development Plan (RPJPN) for 2025-2045. Current film studies predominantly focus on the arts, culture, social issues, gender, communication, history, technical production, and film technology. However, research on film from the perspective of public management is still relatively scarce. This study aims to discover, understand, and explore the concept of strategic management practices for the development of the creative economy in the film sector, specifically within the design of a film curriculum module for students in Banyumas Raya. This is implemented using the collaborative concept of the quadruple helix. The goal is to contribute essential outputs as a repository for themes related to the creative economy in film, an area that remains underrepresented in the literature. Additionally, this study seeks to offer a reference model that can be adopted or modified by other regions in terms of film human resource capacity, accessibility to film education for students, and the practice of collaborative concepts. This research employs a qualitative approach grounded in the new public services paradigm to explore interactions, engagement, roles, contributions, and the dynamics of the helix implementation process among various stakeholders. Data were collected through participant observation, snowball sampling techniques, in-depth interviews with five key informants, and document analysis. Triangulation of data and sources was used to ensure the validity of the data, while naturalness served as a measure of reliability. The findings indicate that the strategic management of film development aims to enhance early critical awareness among young audiences, which in turn strengthens the quality of the film industry, contributing to a healthier film ecosystem in Indonesia's future. The collaborative process has progressed smoothly, without significant obstacles, under the quadruple helix collaboration model. A limitation of this study is the inability to measure the success of this strategy at this time, as the initiative is still in its early stages. Ongoing monitoring and future research are necessary to assess the long-term outcomes of this strategy.